Situation Report: Czechoslovakia, 15 March 1960 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Productivity of Labor and Mechanization under the Forthcoming Five Year Plan Changes in the Slovak Youth Movement Czechoslovak-Yugoslav Cultural Agreement Signed Housing